THE DESIGN, IMPLEMENTATION AND EVALUATION OF INFORMATION SYSTEM FOR ORACLE WORKFORCE DEVELOPMENT PROGRAM (OWDP) CLIENT USING OBJECT APPROACH - Sofi, Nelly (Universitas Gunadarma, 2008)
This research has purposes to developed OWDP information system based on web by using PHP as develop tool’s, to encourage the cource of ORACLE international certification by Gunadarma University until can be access by Internet, to reduce informations delay forparticipant candidates. For design used modelling language taht call UML (UnifedModelling Language). UML is architectur system that works in object oriented analysis design. In this research, using data from samplings that distributed to each participants in OWDP course.Keyword(s) : OWDP. ORACLE, UMLSubject Description: D.2.Software Enginee-ring | D.2.2. Design Tools and Techniques Object-oriented design methods